Assessing causality between different risk factors and pulmonary embolism: A Mendelian randomization study - Jian-ming Wei; Yan-li Song; Huan Zeng; Wen-wen Yan; Xue-bo Liu (Frontiers in Cardiovascular Medicine, 2023)
ObjectivesMendelian randomization (MR) was used to estimate the causal relationship between body mass index (BMI), ever smoked, heart failure, alcohol intake frequency, inflammatory bowel disease (IBD), and pulmonary embolism (PE). This study aimed to investigate whether there is a causal relationship between BMI, the presence of smoking, heart failure, frequency of alcohol intake, IBD, and PE.MethodsPooled data on PE from a published GWAS meta-analysis involving approximately 461,164 participants of European ancestry were selected. A publicly available pooled dataset of BMI (461,460), ever smokers (461,066), heart failure (977,323), IBD (75,000), and frequency of alcohol intake (462,346) was used from another independent GWAS. MR was performed using established analysis methods, including Wald ratios, inverse variance weighted (IVW), weighted median (WM), and MR-Egger. Also, the final expansion was validated with multivariate MR.ResultsIn the IVW model, genetically elevated BMI was causally associated with PE [OR = 1.002, 95% CI (1.001, 1004), P = 0.039]. Cochran’s Q test was used to detect heterogeneity in the MR-Egger analysis (P = 0.576). Therefore, the effect of gene-level heterogeneity was not considered. In the MR analysis of other risk factors, we observed genes for ever smoking [IVW OR = 1.004, 95% CI (0.997, 1.012)], heart failure [IVW OR = 0.999, 95% CI (0.996, 1.001)], IBD [IVW OR = 1.000, 95% CI (0.999, 1.001)], and frequency of alcohol intake [IVW OR = 1.002, 95% CI (1.000, 1.004)] were not causally associated with PE. Analysis using multivariate MR expansion showed no causal effect of BMI on PE considering the effect of height as well as weight (P = 0.926).ConclusionIn European populations, a causal relationship exists between BMI and PE: increased BMI leads to PE. In contrast, ever smoking, heart failure, frequency of alcohol intake, and IBD are not directly associated with PE. There was no causal effect of BMI with PE in multivariate Mendelian randomized analysis.